Free expansion of attractive and repulsive Bose-Einstein condensed vortex states - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2002)
A numerical study of the time-dependent Gross-Pitaevskii equation for an axially symmetric trap to obtain insight into the free expansion of vortex states of BEC is presented. As such, the ratio of vortex-core radius to radia rms radius xc/xrms(<1) is found to play an interesting role in the free expansion of condensed vortex states. the larger this ratio, the more prominent is the vortex core and the easier is the possibility of experimental detection of vortex states.
Keywords: Numerical analysis; Numerical methods; Particles (particulate matter); Superfluid helium; Bose-Einstein condensate; Free expansion; Gross-Pitaevskii equation; Vortex state; Dynamics